The Deadly Effect of Technological Development Online Gambling as Viewed From The Possibility Of Legal Sociology - Frislidia (JLAST : Journal of Law and Social Transformation, 2024)
The shift from conventional togel gaming to internet gambling and its socio-legal ramifications is the main topic of this study, which examines the evolution of gambling activities in Indonesia. Togel gaming was first popular with people who wanted to make quick money. Togel gambling continued despite attempts to stop it, such as demonstrations held under Padang Mayor Fauzi Bahar's administration; frequently, senior law enforcement personnel were said to be involved. With the development of technology and the widespread availability of the internet, togel turned into an online gambling game. Even though it's still illegal, online gambling is nonetheless very common because of its accessibility and inadequate enforcement. The paper highlights difficulties in enforcing the laws by discussing the regulations and penalties related to internet gambling under Indonesian law. Additionally, it looks at the socioeconomic factors—such as financial strains and technological influences—that lead people to gamble online. In order to lessen the negative impacts of internet gambling on Indonesian society, the study's conclusion calls for comprehensive measures to be implemented. It also highlights the significance of legal knowledge, religious education, and societal initiatives.